2002
DOI: 10.1523/jneurosci.22-14-05856.2002
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Calcium-Channel Function inDrosophila: Analysis and Transformation Rescue of Temperature-Sensitive Paralytic and Lethal Mutations ofCacophony

Abstract: Voltage-gated calcium channels play a key role in chemical synaptic transmission by providing the calcium trigger for regulated neurotransmitter release. Genes encoding the primary structural subunit, alpha1, as well as accessory subunits of presynaptic calcium channels have now been identified in a variety of organisms. The cacophony (cac) gene in Drosophila, also known as nightblind A, encodes a voltage-gated calcium-channel alpha1 subunit homologous to vertebrate alpha1 subunits implicated in neurotransmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 61 publications
5
99
1
Order By: Relevance
“…The dab EC1 mutation was recovered in a classic ethane methyl sulfonate mutagenesis screen for modifiers of the TS presynaptic voltage-gated calcium channel α1 subunit mutant cac TS2 (20)(21)(22) that had been recovered previously as a modifier of comatose (23). dab EC1 is an enhancer of cac TS2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The dab EC1 mutation was recovered in a classic ethane methyl sulfonate mutagenesis screen for modifiers of the TS presynaptic voltage-gated calcium channel α1 subunit mutant cac TS2 (20)(21)(22) that had been recovered previously as a modifier of comatose (23). dab EC1 is an enhancer of cac TS2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As described previously (Kawasaki et al, 2002) HC129 . Wild-type flies were Canton S. Stocks and crosses for this study were maintained at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, isolation and analysis of a cac mutant exhibiting rapid temperaturesensitive paralysis has demonstrated that cac encodes a primary presynaptic calcium channel in Drosophila (Dellinger et al, 2000;Kawasaki et al, 2000Kawasaki et al, , 2002. To further examine the role of this calcium channel gene product in neurotransmitter release, we used transgenic methods to express enhanced green fluorescent protein (EGFP)-tagged cac-encoded ␣1 subunits in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, the R876C charge neutralization reduces the sensitivity of the channel to voltage, shifting the conductance-voltage relationship and requiring more depolarization for channel activation. Indeed, the third arginine in the S4 voltage domain has been shown to contribute more than any other S4 charged residue in (19), and the P1385S change found in Dmca1A TS2 (62). B, the Arg-876 amino acid (circled) is conserved in all voltage-gated ion channels through evolution and forms the third charged residue in the S4 voltage sensor transmembrane helix.…”
Section: Fig 1 Temperature-sensitive Mutants Inmentioning
confidence: 99%